Knowledge about obstetric danger signs among pregnant women attending antenatal clinic in a tertiary care hospital of Delhi: a cross sectional study - Kumar, Ashok; Yadav, Geeta; Zutshi, Vijay; Bodat, Suman (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: According to UNICEF, globally 800 million women die due to preventable causes related to pregnancy and childbirth; 20% of which occur in India. It is therefore imperative to understand the level of knowledge about danger signs among pregnant women to augment timely redressal of preventive obstetric causes of mortality. Methods: A hospital based, cross sectional study was conducted at the ANC Clinic in Safdarjung Hospital, New Delhi from 2nd July to 27th July 2018. Convenient sampling was used to identify and interview 354 pregnant women, using a semi structured questionnaire. Data was entered and analysed with SPSSv21. Results were presented as frequencies and proportions. Chi square was used to test for association between qualitative variables, and p-value less than 0.05 was considered significant. Results: 48.3%, 35.6%, and 40.1% of pregnant women had knowledge about danger signs during pregnancy, labour and postpartum respectively. Majority of the women had knowledge about abdominal pain (58.4%) and severe fatigue (80.7%) as danger signs of pregnancy, while bleeding (82.5%) was the most common response as danger sign of labour. More than half had knowledge about heavy bleeding (59.9%) as danger sign of postpartum. The women lacked awareness about Convulsions (92.9%) as danger signs of pregnancy and labour, as well as smelly vaginal discharge (79.6%) in postpartum. Conclusions: Knowledge of obstetric danger signs among pregnant women is still lower. It needs further awareness as it can help in early diagnosis and referral of patients thus reducing maternal mortality and morbidity.